ETIKA PENGURUSAN ISLAM DAN KONVENSIONAL: SATU ANALISIS PERBANDINGAN - Kamri, Nor 'Azzah (Jurnal Syariah, 2019)
This article dicusses the ethical management from Islamic and conventional point of views. There are elements that should be revealed concerning the significance of ethics in determining right and wrong regarding human conduct in organisational context.